PERTANIAN BIOINDUSTRI MENINGKATKAN DAYASAING PRODUK AGROINDUSTRI DAN PEMBANGUNAN PERTANIAN BERKELANJUTAN - Elizabeth, Roosganda; Anugrah, Iwan Setiajie (Universitas Galuh Ciamis, 2020)
The use of bioenergy in agroindustry is predicted to be able to make efficient and effective use of fuel and gas and GMP of its processed products, and to be able to apply the concept of biorefinery to produce food and non-food items of economic value, minimizing energy input (zero waste concept). This paper aims to put out comprehensively the importance of implementing bio-industrial agriculture and related institutional empowerment to increase competitiveness of agroindustrial products for the achievement of sustainable agricultural development. The presentation was carried out using a qualitative descriptive method, which was enriched by a review of various study results and other related literature. The achievement of the utilization of natural resources and human resources in the implementation of sustainable bioindustry agriculture programs to realize food independence and security, in addition to meeting the GMP criteria. Implementation should also include benefits: economic, social, natural resources and environmental sustainability (SDGs), wisely and sustainably. The need for the implementation of the management of natural resources and human resources, the empowerment of the role of institutions, efficiency and effectiveness of alternative and renewable energy, as a producer of agro-industrial products. The need for a alignment of regulations and a holistic and structured development program performance related to regulations, infrastructure and other institutions as well as appropriate: type, time, number and target. With the increase in income and welfare of farmers, it is expected to be able to realize food and energy independence, food security and sustainable bio-industrial agriculture.